Teacher expectations in the early primary grades: A scoping review. Issue 3 (15th November 2022) - Timmons, Kristy; Pyle, Angela; Danniels, Erica; Cowan, Emily; McCann, Allison
Abstract: Teachers are the single most important in‐school factor affecting student learning outcomes. As a result, researchers and policy makers are particularly interested in the ways that teacher‐level factors influence the learning opportunities that teachers provide in their classrooms. A growing body of research suggests that the expectations a teacher sets for individuals and groups of students can significantly affect the learning opportunities that are provided to them. This is highly problematic, especially since teacher expectations can be inaccurate evaluations of student abilities and teacher expectations differentially affect the learning outcomes of racialised students as well as children living in poverty. Much of the research base regarding teacher expectations has focused on upper elementary and secondary grades with little research focus on the ways that teacher expectations are formed and impact children in the first years of formal schooling. Given the potential impact of sustained teacher expectation effects, an in‐depth review of teacher expectation research in the early primary grades is warranted. This study uses a scoping review methodology (H. Arksey and L. O'Malley, 'Scoping Studies: Towards a Methodological Framework, International Journal of Social Research Methodology, 2005, 8(1), 19–32) to analyse research on teacher expectations in the early primary grades. Five themes encapsulate the scope of research published from 2000–2021: (1) teacher expectations of school readiness skills, (2) factors that influence the formation of teacher expectations, (3) teacher expectation effects, (4) stability of teacher expectations, and (5) intervention studies. This paper presents the current state of knowledge surrounding expectations in the early primary grades, as well as highlights challenges in need of further research.